2019
DOI: 10.1371/journal.ppat.1007545
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence, cross antigenicity and circulation sphere of bat-borne hantaviruses revealed by serological and antigenic analyses

Abstract: Bats are newly identified reservoirs of hantaviruses (HVs) among which very divergent HVs have been discovered in recent years. However, their significance for public health remains unclear since their seroprevalence as well as antigenic relationship with human-infecting HVs have not been investigated. In the present study archived tissues of 1,419 bats of 22 species from 6 families collected in 5 south and southwest provinces in China were screened by pan-HV RT-PCR following viral metagenomic analysis. As a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 55 publications
1
12
1
Order By: Relevance
“…In short, we have shown that hantaviruses are infecting bats of different trophic groups (Table ), which is distinct from previous research on Old World bats that found only insectivorous and frugivorous bats to be infected with non‐pathogenic hantaviruses in the genera Loanvirus , and Mobatvirus within the family Hantaviridae (Arai et al, ; Gu et al, ; Guo et al, ; Laenen et al, ; Xu et al, ). Similar studies in southeastern Brazil have shown only phyllostomid bats infected with hantavirus (Araujo et al, ; Sabino‐Santos et al, ).…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…In short, we have shown that hantaviruses are infecting bats of different trophic groups (Table ), which is distinct from previous research on Old World bats that found only insectivorous and frugivorous bats to be infected with non‐pathogenic hantaviruses in the genera Loanvirus , and Mobatvirus within the family Hantaviridae (Arai et al, ; Gu et al, ; Guo et al, ; Laenen et al, ; Xu et al, ). Similar studies in southeastern Brazil have shown only phyllostomid bats infected with hantavirus (Araujo et al, ; Sabino‐Santos et al, ).…”
Section: Resultscontrasting
confidence: 79%
“…Altogether, these results may also indicate that the studied bats can clear the infection, since no viral RNA could be detected. It has been shown that bats can maintain low levels of hantavirus (de Araujo et al, ; Sabino‐Santos et al, ; Xu et al, ), and therefore, our assay may not be sensitive enough for detection, but Xu and others faced the same issues using a ‘pan‐hantavirus’ approach (Xu et al, ). The limitation of our assays may influence in false negative results, new studies focusing in a ‘pan‐hantavirus’ approach are needed in order to identify the hantaviruses circulating among these bats.…”
Section: Resultsmentioning
confidence: 99%
“…The 689 sera used in this study were archived samples stored at -80 o C following collection between 2012 and 2016 in Yunnan, Guangxi, Fujian and Zhejiang provinces, China, and used to investigate group A rotaviruses and hantaviruses in our previous studies (23,35). Bat species were identified as described previously covering 16 species on August 17, 2020 by guest http://jvi.asm.org/ Downloaded from were expressed as described previously (23). In addition, the entire NP of RABV CVS11 strain (GQ918139) was prokaryotically and eukaryotically expressed, with mouse specific hyperimmune sera prepared as before.…”
Section: Sample Informationmentioning
confidence: 99%
“…The details of cross-antigenicity characterization, WB and ELISA assay have been previously described (23). Six mouse specific hyperimmune sera were used to detect the 7 eukaryotically expressed NPs by WB.…”
Section: Cross-antigenicity Analysis By Wb and Serological Assay Of mentioning
confidence: 99%
“…The bats were insectivorous except for one fruit bat species Rousettus leschenaultii in the family Pteropodidae, and were captured in diverse habitats, including natural and artificial caves, orchards and human-made structures (S1 Table). Archived tissues from individual bats had previously been sampled for zoonotic virus surveillance, including for group A rotaviruses (RVA) [32] and hantaviruses [33].…”
Section: Resultsmentioning
confidence: 99%